Sulfur mustard resistant keratinocytes obtained elevated glutathione levels and other changes in the antioxidative defense mechanism. (1st September 2018) - Rothmiller, Simone; Schröder, Sarah; Strobelt, Romano; Wolf, Markus; Wang, Jin; Jiang, Xiqian; Worek, Franz; Steinritz, Dirk; Thiermann, Horst; Schmidt, Annette
Graphical abstract: Highlights: SM resistance induced alterations in the defense against oxidative stress. Glutathione levels were significantly higher in SM-resistant keratinocytes. Nrf2, GST, GCLC and GSR expression was decreased. GST inhibition increased SM sensitivity. Higher levels of MDR1, MDR3 and MDR5 as well as increased NADP + /NADPH ratio. Abstract: Background: Sulfur mustard (SM) is a potent blistering chemical warfare agent, which was first used in 1917. Despite the Chemical Weapons Convention, a use was recently reported in Syria in 2015. This emphasizes the importance to develop countermeasures against chemical warfare agents. Despite intensive research, there is still no antidote or prophylaxis available against SM. Methods: The newly developed SM-resistant keratinocyte cell line HaCaT/SM was used to identify new target structures for drug development, particularly the adaptations in protective measures against oxidative stress. For this purpose, glutathione (GSH) and NAD(P)H levels, the effect of glutathione S-transferase (GST) inhibition as well as activation and expression of Nrf2, GST, glutamate cysteine ligase (GCL) and glutathione-disulfide reductase (GSR) as well as multi-drug resistance (MDR) proteins 1, 3 and 5 were investigated. Results: The HaCaT/SM cells showed not only a better survival after treatment with SM or cytostatic drugs, but also hydrogen peroxide (H2 O2 ). They exhibit more GSH even after SM treatment. Nrf2 levels were significantly lower. Inhibition of GST led to significantly decreased, activation to slightly higher IC50 values after SM treatment and a lower expression of GST was observed. The cells also expressed less GCLC and GSR. Expression of MDR1, MDR3 and MDR5 was higher under control conditions, but less stimulated by SM treatment. An increased NADP + /NADPH ratio as well as higher NAD + levels were shown. Conclusion: In summary, an improved response of the resistant cell line to oxidative stress was observed. The underlying mechanisms are elevated GSH levels as well as lower expression of Nrf2 and its targets GCLC and GST as well as GSR and MDR1, MDR3 and MDR5. GST is an especially interesting target because its inhibition already induced a significant SM sensitivity. SM resistance also caused redox equivalent level differences. Taken together, these findings provide further insight into the mechanism of SM resistance and may open a window for novel therapeutic targets in SM therapy.